Space 2030 tackling society's challenges (OECD, 2005)
This book explores the contribution space systems might make in dealing with looming societal challenges related to threats to the physical environment and the management of natural resources, growing mobility and its consequences, increasing security concerns, and the shift to the information society. It discusses the challenges for developing space applications. It assesses the strengths and weaknesses of the institutional, legal and regulatory frameworks that currently govern space activities in the OECD area and beyond. Finally, it formulates an overall policy framework that OECD governments might use in drafting policies designed to ensure that the potential that space has to offer is actually realized.--Publisher's description.